2012
DOI: 10.1089/neu.2011.2152
|View full text |Cite
|
Sign up to set email alerts
|

Mild Hyperthermia Worsens the Neuropathological Damage Associated with Mild Traumatic Brain Injury in Rats

Abstract: The effects of slight variations in brain temperature on the pathophysiological consequences of acute brain injury have been extensively described in models of moderate and severe traumatic brain injury (TBI). In contrast, limited information is available regarding the potential consequences of temperature elevations on outcome following mild TBI (mTBI) or concussions. One potential confounding variable with mTBI is the presence of elevated body temperature that occurs in the civilian or military populations d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 81 publications
0
46
0
Order By: Relevance
“…To determine if hyperthermia in combination with a mTBI worsens cognitive recovery, we utilized the parasagittal fluid-percussion injury (FPI) model in adult male Sprague Dawley rats ( n =61, 2–4 mos, Charles Rivers Laboratories, Wilmington, MA, USA). Animals were anesthetized (70% nitrous oxide, 1–3% isoflurane, and 30% oxygen) 24 h prior to injury and surgically prepared for FPI as previously described (Sakurai et al, 2012; Titus et al, 2013). Briefly, anesthesia was induced with 3% isoflurane, 70% nitrous oxide and 30% oxygen, and animals were maintained at 1–2% isoflurane, 70% nitrous oxide and 30% oxygen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine if hyperthermia in combination with a mTBI worsens cognitive recovery, we utilized the parasagittal fluid-percussion injury (FPI) model in adult male Sprague Dawley rats ( n =61, 2–4 mos, Charles Rivers Laboratories, Wilmington, MA, USA). Animals were anesthetized (70% nitrous oxide, 1–3% isoflurane, and 30% oxygen) 24 h prior to injury and surgically prepared for FPI as previously described (Sakurai et al, 2012; Titus et al, 2013). Briefly, anesthesia was induced with 3% isoflurane, 70% nitrous oxide and 30% oxygen, and animals were maintained at 1–2% isoflurane, 70% nitrous oxide and 30% oxygen.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, in individuals that are engaged in strenuous activities including exercise, competitive sports or under highly stressful conditions, core temperatures may reach mildly hyperthermic levels that could potentially alter traumatic consequences. In a recent study, our laboratory first reported that artificially elevating brain temperature to 39 °C before mTBI significantly increased patterns of neuronal death within cortical and subcortical regions as compared to normothermic mTBI (Sakurai et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…However, limited information is available regarding the potential consequences of secondary hyperthermia on outcomes following mild TBI. Fortunately, recent research by Sakurai et al [72] combined mild FPI with PTH in rats. Elevation in brain temperature after mild TBI was apparently shown to aggravate pathological damage.…”
Section: Experimental Model Of Tbi Complicated By Hyperthermiamentioning
confidence: 99%
“…15 To our knowledge, however, they have not been described following mild TBI within the context of exercise. Here we describe the HR, CBT, and ambulatory activity during exercise regimens that elicit a low or high stress response.…”
Section: Introductionmentioning
confidence: 96%
“…A recent study utilizing an experimental mild TBI demonstrated that peritraumatic mild hyperthermia increased cortical contusion size. 15 …”
mentioning
confidence: 99%